2002
DOI: 10.1046/j.1365-2788.2002.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with learning difficulties and their support networks

Abstract: Mothers with learning difficulties are thought to be among the most socially isolated parents in the community. A great deal of attention has been directed to assessing their parenting abilities and teaching parenting skills, but less has been given to the support that mothers may (or may not) receive from family, friends and the service system. The present paper investigates mothers' views about the types of support which they receive and from whom they receive it. Data were derived from 70 mothers who partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
1
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 36 publications
8
83
1
10
Order By: Relevance
“…They all perceived and could also articulate a need for support, seeking help when a situation was experienced as difficult. Informal good-quality support networks have been found to be important for the well-being of both children and parents in general, and their special significance for families with parents with intellectual disability has been shown in previous research (Llewellyn 1995;McGaw 2000;Llewellyn and McConnell 2002). In line with these findings, the mothers interviewed for this research reported having received useful advice and support through such networks, including the provision of parenting models helping them to strengthen their own parenting skills and reduce some of their barriers to parenthood.…”
Section: Strategies Used To Obtain Supportmentioning
confidence: 80%
“…They all perceived and could also articulate a need for support, seeking help when a situation was experienced as difficult. Informal good-quality support networks have been found to be important for the well-being of both children and parents in general, and their special significance for families with parents with intellectual disability has been shown in previous research (Llewellyn 1995;McGaw 2000;Llewellyn and McConnell 2002). In line with these findings, the mothers interviewed for this research reported having received useful advice and support through such networks, including the provision of parenting models helping them to strengthen their own parenting skills and reduce some of their barriers to parenthood.…”
Section: Strategies Used To Obtain Supportmentioning
confidence: 80%
“…Pequena rede de apoio também foi encontrada em estudos anteriores (Aunos et al, 2008;Guinea, 2001;Kroese et al, 2002;Llewellyn & McConnell, 2002). No que diz respeito a quem fornece apoio para as mães, os resultados obtidos concordam com a literatura da área, sendo o apoio advindo majoritariamente de membros da família, com rara ajuda de amigos e vizinhos (Aunos et al, 2008;Guinea, 2001;Kroese et al, 2002;Llewellyn, 1995;Llewellyn & McConnell, 2002;Postalli et al, 2011;Traustadóttir & Sigurjónsdóttir, 2008). Desnecessário dizer que as pessoas que oferecem apoio não são pagas por essa ajuda, apesar de serem envolvidas e fundamentais para mães com defi ciência intelectual.…”
Section: Discussionunclassified
“…Em relação aos indivíduos com defi ciência intelectual, além de fornecerem tais benefícios, as redes de apoio podem ser responsáveis pela melhoria da qualidade de vida e pela manutenção da saúde física e mental e do bem-estar (Booth & Booth, 1994;Kroese, Hussein, Clifford, & Ahmed, 2002;Llewellyn & McConnell, 2002;McConnell, Dalziel, Llewellyn, Laidlaw, & Hindmarsh, 2009). Podem também estar relacionadas a estilos positivos de interação entre a mãe defi ciente e seus fi lhos (Feldman, Varghese, Ramsay, & Rajska, 2002), e à compensação de limitadas habilidades parentais (Llewellyn & McConnell, 1998).…”
unclassified
See 1 more Smart Citation
“…Ce type de soutien est encore mieux accueilli lorsque son actualisation rehausse leur confiance en leurs compétences parentales et s'arrime à leurs attentes et à leurs valeurs (Llewellyn, 1995). Or plusieurs parents présentant une DI/LI n'ont aucun ou très peu de contacts avec leur famille élargie (Llewellyn et McConnell, 2002). D'autres n'apprécient pas l'attitude de leurs proches lorsqu'ils ont des comportements semblant témoigner d'une disqualification de leurs pratiques et de leurs compétences parentales (Mayes et al, 2008;.…”
Section: Ressourcesunclassified